Biomechanical Assessment of Vertebroplasty Combined with Cement-Augmented Screw Fixation for Lumbar Burst Fractures: A Finite Element Analysis - Yueh-Ying Hsieh; Yi-Jie Kuo; Chia-Hsien Chen; Lien-Chen Wu; Chang-Jung Chiang; Chun-Li Lin (Applied Sciences, 2020)
A hybrid fixation method, using a combination of vertebroplasty and cement-augmented screws, has been demonstrated as a useful technique for securing osteoporotic burst fractures. The purpose of this study was to assess changes in the range of motion (ROM) and stress in the spine after treating a lumbar burst fracture with this hybrid method. Five finite element models were developed: (a) intact lumbar spine (INT), (b) INT with vertebroplasty at L3 (AwC), (c) two-segment fixation of AwC (AwC-TSF), (d) AwC-TSF model with cement-augmented screws (AwC-TSF-S), and (e) INT with an L3 burst fracture treated with two-segment fixation (TSF). After loading, the models were evaluated in terms of the ROM of each motion segment, stiffness of fusion segments, and stresses on the endplates and screws. The results showed that the TSF model has a larger ROM at the instrumented segments than both the AwC-TSF and AwC-TSF-S models. The stiffness at L2–L4 under extension and lateral bending in AwC-TSF, AwC-TSF-S and TSF was approximately nine times greater than the INT model. In conclusion, the hybrid fixation method (AwC-TSF-S) results in a stiffer construct and lower ROM at instrumented segments, which may also reduce the risk of fracture of adjacent vertebrae.